Pemberdayaan Masyarakat Oleh PT Nestle Indonesia Melalui Kelompok Tani Ternak Sapi Perah Budi Luhur. (Jurnal Ilmu Kesejahteraan Sosial, 2018)
Poverty is a social welfare issue and has become the focus of world development. The most basic form of poverty is the deprivation of welfare. Poverty is experienced by many developing countries like Indonesia and nowadays it is centered in rural areas. Therefore, PT Nestle as part of the private sector has an obligation to support and help solve poverty experienced by the state. The manifestations of these efforts are to support community empowerment through Budi Luhur Dairy Farmers Group --- as one of the strategies to reduce poverty. Why is it focused on dairy farmers? Because they increase the need for human beings in the framework of human investment. Budi Luhur is one of the successful groups of dairy farmers in the East Java. The success of Budi Luhur Dairy Farmer Group was also due to the help and role of PT Nestle who actively participated the empowerment activities. Hence, it is interesting to see further the process of empowerment by Nestle Corp through Budi Luhur Group. The method used is the qualitative approach in order to get deeper result. Based on research, the empowerment carried out by Nestle Corp produced a positive impact for the farmers to reduce poverty and unemployment exactly in in rural areas. However, the form of empowerment program provided is so far still limited to providing subsidies to support dairy farm activities assistance in the form of equipment.